KESAN INTERAKSI PENDEKATAN PEMBELAJARAN DAN FAKTOR JANTINA PELAJAR KE ATAS PENCAPAIAN SUBJEK KIMIA MELALUI KAEDAH PBL via FACEBOOK - Mohamed Sunar, Mohd Shahir; Shaari, Ahmad Jelani (Journal of Techno-Social, 2018)
The influence of social media such as Facebook in various fields including the field of education cannot be denied. The primary objective of this study is to examine the interaction effects of students’ learning approach and their gender on the achievement of chemistry subject using methods of problem-based learning via Facebook. The sample consisted of 120 students from Kolej MARA who were randomly selected to undergo treatment PBL via Facebook for nine weeks. This quantitative study using experimental design with factorial 2x2. The main effects studied were students’ learning approaches (surface and deep) and gender (male and female) and both interaction on the achievement of final chemistry examination. Descriptive analysis showed a shifted of students’ surface learning approach to deep learning approach after treatment PBL via Facebook. Results of Two-Way ANOVA test showed that the main effect of students’ learning approach on the student achievement is significant across gender. However, the main effect of gender and the impact of the interaction between the two independent variables on student achievement is not significant. The results of this study are important because PBL via Facebook has been found to have the ability to encourage the transition from surface learning approach to deep learning approaches among students. The deep learning approach then enables students to obtain better academic achievement.